Effect of Relationship Marketing on Word of Mouth in Life Insurance with the Approach of Trust and Commitment: Case Study of Karafarin Insurance Agents in Mashhad - Saeed Parsa; Tooraj Sadeghi (International Journal of Management, Accounting and Economics, 2015)
Word of mouth is of critical importance for marketers and many scholars believe that word of mouth is one of the most effective and efficient advertising ways. Moreover, relationship marketing causes the costs of attracting new customers through long-term relationships with current customers and in this way increases firm profitability. Indeed, relationship marketing leads to customer satisfaction and loyalty through creating commitment and trust. Loyal customer also influences company’s word of mouth. Thus, this research conducted focused on studying the effect of relationship marketing on life insurance word of mouth. This is an applied research; and is a descriptive, filed study. Research statistical population was life insurance clients of Karafarin Insurance Agents in Mashhad. 384 individuals selected as research sample through simple random sampling method. Data collected through questionnaire. Questionnaire reliability measured through using Cronbach alpha. Research hypotheses also were tested by structural equation modeling (SEM). The results of analyzing research hypotheses indicated that relationship marketing directly influences life insurance word of mouth. In addition, customers’ trust also influences their satisfaction of buying life insurance. Customers’ commitment influences their satisfaction of buying life insurance; furthermore, customers’ satisfaction influences customers’ loyalty to buy life insurance. And finally, customers’ loyalty influences life insurance word of mouth.